PENANGANAN GIZI PADA CELIAC DISEASE - Goi, Misrawatie (JOURNAL HEALTH AND NUTRITIONS, 2017)
ABSTRACT Celiac disease occurs in 1% of the child and adult population. In adulthood, there are 2-3 times more women than men. The disease is not only known in Europe but also in the Middle East, Asia, America, and Africa. Although many people are exposed to this disease and the incidence rate is increasing, there is still a lot of underdiagnoses, although even in one country in Europe it is reported that there is 1 sufferer to 77 people. In Indonesia until now, the exact number of cases is still not known, but allegedly the number is not far from 1 compared to 100 people. The authors conducted a study on patients with difficulty eating in children who seek treatment at Picky Eaters Clinic Jakarta (Clinic Special Difficulty Eating In Children). Allegedly, about 34% of the population, who is difficult to eat, is children with Celiac disease. The assumption is based on the benefits of gluten-free in those children diet. Celiac disease, is often called gluten intolerance, celiac sprue, non-tropical sprue, endemic sprue, gluten enteropathy or gluten-sensitive enteropathy. Those refer to a disease in which gluten intolerance (a protein) occurs, leading to changes in the small intestine resulting in impaired nutrient absorption and various disorders in the function of the human body. Celiac disease is a long-term and permanent hereditary disease. Keywords: celiac disease, gluten ABSTRAK Celiac disease terjadi pada 1% di antara populasi anak dan dewasa. Pada usia dewasa terdapat 2-3 kali lebih banyak perempuan dibandingkan laki-laki. Penyakit ini tidak hanya dikenal di Eropa tetapi juga di Timur Tengah, Asia, Amerika dan Afrika. Meskipun banyak manusia terkena penyakit ini dan angka kejadian semakin meningkat, tetapi masih banyak terjadi underdiagnosis, meskipun bahkan di salah satu negara di Eropa dilaporkan terjadi 1 penderita pada 77 orang. Di Indonesia sampai sekarang masih belum diketahui pasti angka kejadiannya, tetapi diduga angkanya tidak jauh dari 1 dibandingkan 100 orang. Penulis mengadakan penelitian pada penderita kesulitan makan pada anak yang berobat di Picky Eaters Clinic Jakarta (Klinik Khusus Kesulitan Makan Pada Anak) diduga sekitar 34% dari populasi anak sulit makan tersebut adalah penderita penyakit seliak, karena saat dilakukan penghindaran terhadap diet gluten terdapat perbaikan klinis yang bermakna. Celiac disease atau sering juga disebut gluten intolerance, celiac sprue, nontropical sprue, endemic sprue, gluten enteropathy atau gluten-sensitive enteropathy merupakan suatu penyakit dimana terjadi intoleransi terhadap gluten (sejenis protein), yang menyebabkan perubahan dalam usus halus sehingga terjadi gangguan penyerapan nutrisi yang masuk ke tubuh sehingga menyebabkan berbagai gangguan pada fungsi tubuh manusia. Celiac disease merupakan penyakit keturunan dan permanen yang bersifat jangka panjang. Kata Kunci: celiac disease, gluten